Treatment experience of people living with HIV who transitioned from oral to long-acting injectable antiretrovirals in Puerto Rico: A qualitative study - Robert A. Velez; Georgina Silva-Suarez; Kalumi Ayala; Yarelis Alvarado; Felix Badillo (PLoS ONE, 2025)
This study explores the treatment experience of people living with HIV who transitioned from oral ART to long-acting injectable therapy Cabotegravir/Rilpivirine (LAI-CAB/RPV) in Puerto Rico. Interpretative Phenomenological Analysis was used to explore the lived experiences of people with HIV 21 years old or older who transitioned from oral ART to LAI-CAB/RPV. Purposeful sampling was used to recruit study participants. Ten in-depth interviews were conducted at the clinic, audio recorded, and transcribed verbatim. Participants’ mean age was 67 years (±9), most were men (70%), and most identified themselves as heterosexual (60%). On average, they have taken oral ART for 23.2 years ± 8.7. The transition to LAI-CAB/RPV marked a profound positive change; for them, injectable ART means “freedom,” improving their quality of life, providing relief, and a sense of “normalcy.” Adherence remained robust, marked by consistent appointment attendance. They overwhelmingly encouraged others to embrace the transition, highlighting its transformative impact on their lives. Study participants’ positive experiences underscore the potential of LAI-CAB/RPV to revolutionize the standard of care, enhancing both the treatment experience and the overall well-being of people living with HIV. Continued research is crucial to refine and expand the benefits of this treatment approach.